Knowledge Proficiency of Disaster Mitigation in Deaf Students - Christianingsih, Siska; Fauzi, Abdul; Kholis, Anja Hesnia; Hilfida, Nurulia Hanum; Saudi, La; Ridlo, Muhamad Ridlo (International Conference on Biomedical and Sports Medicine, 2025)
Indonesia is prone to natural disasters, and the deaf community is a particularly vulnerable group. Disaster education in schools is crucial for improving preparedness, especially for deaf students, and for achieving inclusive disaster risk reduction. This study aimed to assess the knowledge level of disaster mitigation among deaf students at Karya Mulia Inclusive Senior High School in Surabaya. Using a cross-sectional design and total sampling, 41 students from grades X to XII participated. A structured questionnaire was used to evaluate their disaster mitigation knowledge. Results revealed that 56.1% of students had poor knowledge, 43.9% had sufficient knowledge, and none demonstrated good knowledge. This highlights a critical gap in the integration of disaster education in special education settings. The study emphasizes the need for structured, disability-inclusive disaster education using adaptive media, visual aids, simulations, and teacher empowerment to improve preparedness among deaf students.